Preventing Child Marriage in Indonesia: An Analysis of Government Policies, Institutional Challenges, and Strategic Efforts - Muhamad Kholid; Abdulah Safe'i; Jaenudin Jaenudin; Agi Attaubah Hidayat; Endang Isak (Hukum Keluarga Islam IAIN LANGSA, 2025)
This study critically examines the Indonesian central government’s policies, institutional challenges, and strategic interventions in mitigating child marriage—a pervasive issue with documented repercussions for health, education, gender equality, and national development. Employing an empirical juridical approach, the research integrates qualitative descriptive analysis with primary data from field observations and semi-structured interviews with officials at the Ministry of Women’s Empowerment and Child Protection (KP3A RI) and the Directorate General of Religious Courts (Ditjen Badilag). Secondary data derive from legislative reviews, judicial records, and scholarly literature. Thematic analysis contextualizes findings within Indonesia’s legal pluralism and decentralization framework. KP3A RI has made preventing child marriage one of its five main national programs. This effort is supported by six key initiatives, such as community-based (Integrated Child Protection by Communities/PATBM) and mobile protection services like MOLIN and TORLIN (Women and Children Protection Motor and Mobile Units). The Supreme Court’s Regulation (PERMA No. 5/2019) requires courts to focus on children’s best interests when deciding on marriage dispensation requests. However, this rule does not become a primary reference. In 2021, religious courts approved 95% of the 61,443 dispensation requests they received. There are also broader challenges. Many villages now have more control over their budgets. However, funds have often been used for economic recovery instead of child protection after the pandemic. There are also gaps in the rules about when dispensations can be granted. Several strategies are being used to address these issues. These include (1) Multi-sector coordination through the Joint Movement for Child Marriage Prevention (Geber PPPA) movement; (2) Training and community programs like Children’s Forums and family learning (Puspaga) centers; and (3) new draft regulations to tighten dispensation procedures. Although Indonesia has a strong and united policy approach, results are limited by uneven local implementation and courts being too lenient. For lasting progress, the country needs (1) better and shared data systems, (2) stronger financial accountability at the village level, and (3) judicial training to focus on child protection rather than social or cultural pressures. The study highlights the need for strong, coordinated leadership to overcome local differences and ensure national child marriage prevention standards are fully applied at the community level.